Big results now? Emerging lessons from results-based aid in Tanzania - Heiner Janus; Niels Keijzer (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
Ongoing experiments with results-based aid (RBA), a development cooperation modality that disburses grants or loans in response to the achievement of pre-defined results, constitute an important and influential trend in international development cooperation. This discussion paper seeks to contribute to the emerging literature that assesses the wide-ranging RBA experiments by different donors. The paper analyses design features and initial implementation experiences of three ongoing RBA programmes in Tanzania that support government reforms in the water, education and decentralisation sectors. In addition to their design elements, these three programmes share a common context in the Big Results Now! (BRN) programme, which the government launched in 2013 to improve the provision of public services. Based on its analysis, with particular attention to the specific capacity development support related to the RBA programmes, this paper concludes that the overarching BRN set-up as well as the nature of capacity development support clearly prioritises short-term gains over longer-term sustainability. More importantly though – and given the overall context and interests of all involved – the paper suggests that these tendencies are not intrinsic to RBA as a modality but rather a more common feature of development cooperation as such.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Wirksamkeit und Evaluierung